Consistency of Social Interactions in Sooty Mangabeys and Chimpanzees - Mielke, Alexander; Preis, Anna; Samuni, Liran; Gogarten, Jan F.; Lester, Jack D.; Crockford, Catherine; Wittig, Roman M. (Frontiers in Ecology and Evolution, 2021)
Predictability of social interactions can be an important measure for the social complexity of an animal group. Predictability is partially dependent on how consistent interaction patterns are over time: does the behaviour on one day explain the behaviour on another? We developed a consistency measure that serves two functions: detecting which interaction types in a data set are so inconsistent that including them in further analyses risks introducing unexplained error; and comparatively quantifying differences in consistency within and between animal groups. We applied the consistency measure to simulated data and field data for one group of sooty mangabeys (Cercocebus atys atys) and to groups of Western chimpanzees (Pan troglodytes verus) in the Taï National Park, Côte d’Ivoire, to test its properties and compare consistency across groups. The consistency measures successfully identified interaction types whose low internal consistency would likely create analytical problems. Species-level differences in consistency were less pronounced than differences within groups: in all groups, aggression and dominance interactions were the most consistent, followed by grooming; spatial proximity at different levels was much less consistent than directed interactions. Our consistency measure can facilitate decision making of researchers wondering whether to include interaction types in their analyses or social networks and allows us to compare interaction types within and between species regarding their predictability.